Women and the Challenges of the Future of Islamic Education - Manshur, Fadlil Munawwar; Herlina, N. Hani; Atoillah, Ahmad Nabil (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2020)
This study seeks to elaborate on the position and function of women in the realm of Islamic education. This study uses the critical review method, a method used to interpret texts critically. The results of the study show that Muslim women in Indonesia are in fact part of Muslim women in other parts of the world. However, Indonesian Muslim women tend to have greater opportunities and chances in facing a bright future of education. Within Islamic education institutions, the viewpoint of women has shifted from a conservative view to a more egalitarian one. The oldest and largest Islamic education institution in Indonesia, namely pondok pesantren, is accustomed in using the terminology of equality and alignment relatives to gender as their educational discourse. They are not only fluent in discussing the concept of gender equality, the terminology has even become part of the practice of pondok pesantren education.